WRITING SOCIOLOGICAL CRIME FICTION: YOU WILL HAVE YOUR DAY IN COURT - Crockett Thomas, Phil (Art/Research International)

(untitled) (University of Alberta, 2021)
In this article I share and discuss a poetic work of experimental sociological crime fiction titled “You Will Have Your Day in Court” (in Crockett Thomas, 2020c). In it I reimagine the “true crime” story of “King Con” Paul Bint, who for a period in 2009 successfully impersonated Keir Starmer, the then Director of Public Prosecutions. I first introduce my collaborative approach to writing sociological crime fiction, connections to poststructuralist philosophy and conceptualisation of research as a process of translation. After sharing the piece, I discuss thematic aspects of the work, such as the popular fascination of fraud, desire for explanations for criminal acts, and the narrative constraints placed on people who have experienced criminalisation. I also consider stylistic elements including use of narrative voice, characterisation, and narrative structure. I hope that this article is of interest to scholars aiming to marry poststructuralist thought with an experimental approach to writing sociological fiction.